Impact of Hypertension and Physical Fitness on SARS-COV-2 and related Consequences. (Possible mechanisms with focusing on ACE2) - Mehdi Kushkestani; Mohsen Parvani; Mahsa Moghadassi; Yaser Kazemzadeh; Kiandokht Moradi (Babol University of Medical Sciences, 2022)
Hypertension disease as an absolute risk factor of Covid-19 disease has been well-proven in recent evidence. The factors such as the use of antihypertensive drugs, protein expression, and compensatory axes resulted in hypertension disease playing very important roles in the occurrence of this problem. In this review study, we first attempted to investigate the higher chance reason for Covid-19 disease in people with high blood pressure; then we examined the related mechanisms, and finally, we reported the differences and similarities between people with high blood pressure and athletes. All in all, we concluded that people who exercise regularly, the same as hypertensive patients (Compensatory mechanism) are more susceptible to COVID-19 infection due to the high concentration of ACE2 (Physiological mechanism) caused by exercise adaptation, but for the low level of ANG2 (Systematic and gene expression) these individuals (Active subjects) indicate fewer complications and severity symptoms of COVID-19  such as dyspnea, hospitalization and, heart disease compared with hypertensive patients.